2019
DOI: 10.1016/j.heliyon.2019.e03023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microbial community during dry storage and recovery of aerobic granular sludge

Abstract: A B S T R A C TAerobic granular sludge (AGS) was imbedded in agar and stored at 4 C for 30 days, and then the stored granules were recovered in a sequencing batch reactor fed real wastewater within 11 days. Variations in microbial community compositions were investigated during dry storage and recovery of AGS, aiming to elucidate the mechanism of granular stability loss and recovery. The storage and recovery of AGS involved microbial community evolution. The dominant bacterial genera of the mature AGS were Zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 71 publications
1
7
0
3
Order By: Relevance
“…It has been suggested that Proteobacteria play an important role in the energy producing metabolism of nitrogen sources. 41 The second dominant phylum of all gel beads was Actinobacteriota (39.67%, 35.83%, 33.34%, and 29.15%, respectively), which was decreased compared to the inoculum activated sludge (44.17%). Studies have reported that Actinobacteria mostly play the role of decomposers in nature, and are a versatile hydrocarbon degrader.…”
Section: Resultsmentioning
confidence: 89%
“…It has been suggested that Proteobacteria play an important role in the energy producing metabolism of nitrogen sources. 41 The second dominant phylum of all gel beads was Actinobacteriota (39.67%, 35.83%, 33.34%, and 29.15%, respectively), which was decreased compared to the inoculum activated sludge (44.17%). Studies have reported that Actinobacteria mostly play the role of decomposers in nature, and are a versatile hydrocarbon degrader.…”
Section: Resultsmentioning
confidence: 89%
“…These bacteria appeared to be outcompeted by other carbon degraders after phase IV. Possible competitors of Chryseobacterium were the filamentous bacteria Haliscomenobacter, known to have proteolytic activity (Parte et al, 2010), but also Ferruginibacter and Taibaiella, known aerobic heterotrophs found in AGS processes with hydrolytic activity (McBride et al, 2014;Szabó et al, 2017;Zhang et al, 2019). The ability to degrade complex substrates might have also led to the enrichment of members of the Cytophagaceae family during phase IV, associated to the hydrolysis of proteins and polysaccharides in biological processes (McBride et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas and Thauera, as both HB and PAO [39,40], could favor efficient organics and phosphorus removal, which were found to be much more abundant under non-aeration conditions (R2) than in aeration conditions (R1). A higher abundance of Aquimonas and Acinetobacter in R2 than R1 might also contribute to organics degradation and phosphorus removal, respectively [34,41]. Overall, the higher abundance of both HB and PAO in R2 than in R1 could be responsible for the better organics and phosphorus removal under non-aeration conditions than in aeration conditions for the recovered MBGS.…”
Section: Potential Functional Characteristics Of Microorganismsmentioning
confidence: 97%
“…Meanwhile, Firmicutes, Actinobacteria and Clostridia decreased substantially (Figure 3a,c). However, more Clostridia (39.31%) belonging to phylum Firmicutes (39.34%) in R0 indicated the presence of more anaerobic and facultative anaerobic bacteria during the storage period [34,35]. In addition, representatives of Burkholderiaceae, Xanthomonadaceae and Sphingomonadaceae belonging to phylum the Proteobacteria were identified.…”
Section: Microbial Community Successionmentioning
confidence: 99%